Wireless Sensor Networks Principles, Design and Applications - Yang, Shuang-Hua.; SpringerLink (Online service) (London : Springer London : Imprint: Springer, 2014)
Wireless Sensor Networks presents the latest practical solutions to the design issues presented in wireless-sensor-network-based systems. Novel features of the text, distributed throughout, include workable solutions, demonstration systems and case studies of the design and application of wireless sensor networks (WSNs) based on the first-hand research and development experience of the author, and the chapters on real applications: building fire safety protection; smart home automation; and logistics resource management. Case studies and applications illustrate the practical perspectives of: ·         sensor node design; ·         embedded software design; ·         routing algorithms; ·         sink node positioning; ·         co-existence with other wireless systems; ·         data fusion; ·         security; ·         indoor location tracking; ·         integrating with radio-frequency identification; and ·         Internet of things Wireless Sensor Networks brings together multiple strands of research in the design of WSNs, mainly from software engineering, electronic engineering, and wireless communication perspectives, into an over-arching examination of the subject, benefiting students, field engineers, system developers and IT professionals. The contents have been well used as the teaching material of a course taught at postgraduate level in several universities making it suitable as an advanced text book and a reference book for final-year undergraduate and postgraduate students.  .
Part I: Principles of WSNs -- An Introduction to WSNs -- Principles of WSNs -- Part II: WSN Design -- WSN Hardware Design -- Embedded Software Design for WSNs -- Routing Technologies in WSNs -- Optimisation of Sink-node Positioning in WSNs -- Co-existence of WSNs -- Sensor Data Fusion in WSNs -- Security in WSNs -- Part III: WSN Application Technologies -- Indoor Location Tracking -- Hybrid WSNs for Logistics Management -- Internet of Things -- ZigBee Smart Home Automation: IndeedNET -- Building Fire Safety Protection: SafetyNET -- Conclusions.
Keywords: Electrical engineering; Computer communication systems; Electronic circuits; Application software; Communications Engineering, Networks; Computer Communication Networks; Circuits and Systems; Information Systems Applications (incl. Internet).